2012
DOI: 10.1016/j.brainres.2012.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation to cues predicting inescapable delay in adolescent Attention Deficit/Hyperactivity Disorder: An fMRI pilot study

Abstract: No Escape compared to Escape Delay trial cues in the insula, amygdala, ventral striatum and orbito-frontal cortex. Conclusion:The results of this pilot study provides further evidence for the role of altered motivational systems in ADHD and the most direct evidence for a biological basis of delay aversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 87 publications
3
45
3
Order By: Relevance
“…Indeed, striatal structures are known to show biphasic responses, making them capable of responding to positive (reward) as well as negative (punishment) stimulation. 47 Moreover, such an account would be in line with experimental findings demonstrating increased responses in reward processing brain regions to delayed rewards 39 . Yet, both reward magnitude and reward probability are coded relatively rather than absolutely.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Indeed, striatal structures are known to show biphasic responses, making them capable of responding to positive (reward) as well as negative (punishment) stimulation. 47 Moreover, such an account would be in line with experimental findings demonstrating increased responses in reward processing brain regions to delayed rewards 39 . Yet, both reward magnitude and reward probability are coded relatively rather than absolutely.…”
Section: Discussionsupporting
confidence: 64%
“…Alternatively, they might be unable to correctly establish an association between a reward-predicting cue and the receipt, leading to an increased prediction error response during reward receipt relative to non-reward. A third explanation would be that participants with ADHD experience the inability to gain reward as overly aversive, which may result in a stronger signal of the brain to avoid such a situation in future 39 .…”
Section: Discussionmentioning
confidence: 99%
“…For the sake of completeness, two additional published fMRI studies should be mentioned, although they focused on different aspects of reward/motivational processing (Lemiere et al, 2012; Wilbertz et al, 2012). The study by Wilbertz et al exclusively focused on reward delivery rather than reward anticipation and found no differences in the VS, replicating the finding of Scheres et al (2007).…”
Section: Bold Fmri Studies On Reward Processing In Adhdmentioning
confidence: 99%
“…For example, Plichta and colleagues (2009) identified increased activity in amygdala in adults with ADHD comparing to healthy controls during the choices of delayed rewards. Lemiere et al (2012) found increased insula and amygdala activity during the anticipation of an inescapable delay. Wilbertz and colleagues (2013) reported a positive association between the activity in inferior temporal cortex and right amygdala and the length of delayed period within the ADHD but not the control group.…”
Section: Discussionmentioning
confidence: 90%
“…delay aversion; Sonuga-Barke, 2002) mediated by hyper-activation within the brain's emotion centres (e.g. insula and amygdala; Lemiere et al, 2012;Plichta et al, 2009;Wilbertz et al, 2013). Interestingly, the potential role of intrinsic brain activity during the process of waiting in individuals with ADHD has not been investigated.…”
Section: Introductionmentioning
confidence: 99%